Importance of Small-Scale Food Crop Models in Urban and Peri-Urban Contexts - Hernández Durán, Hernán José (Darul Yasin Al Sys, 2025)
The rapid urbanization of the 21st century has significantly reshaped global food production and consumption patterns, with profound implications for food security and sustainability, particularly in developing countries. With over 56% of the global population now residing in urban areas (World Bank), cities have become increasingly dependent on rural agricultural systems and food imports. This reliance leads to elevated transportation costs, higher carbon emissions, and heightened vulnerability to global supply disruptions. In response, small-scale food production within urban and peri-urban environments presents a promising solution. Models such as community gardens, rooftop farms, and family farming initiatives not only decrease dependence on external food sources but also support environmental sustainability, bolster local economies, and improve urban residents’ quality of life. Despite these benefits, the implementation of urban agriculture faces considerable challenges, including limited access to cultivable land, inadequate infrastructure, and regulatory constraints. Public perception and community engagement are critical factors influencing the adoption and long-term viability of these practices. This article explores the role and impact of urban agriculture in addressing food insecurity, with a specific focus on San Miguel, El Salvador. It highlights the potential of agro-architectural innovations and community-based approaches in enhancing urban resilience and sustainability. The study concludes with strategic recommendations to foster broader adoption of urban agricultural practices through supportive policies, infrastructure development, and awareness campaigns.